2008
DOI: 10.1016/j.nut.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary fiber and markers of systemic inflammation in the Women's Health Initiative Observational Study

Abstract: Objective-Systemic inflammation may play an important role in the development of atherosclerosis, type 2 diabetes, and some cancers. Few studies have comprehensively assessed the direct relationships between dietary fiber and inflammatory cytokines, especially in minority populations. Using baseline data from 1,958 postmenopausal women enrolled in the Women's Heath Initiative Observational Study, we examined cross-sectional associations between dietary fiber intake and markers of systemic inflammation (includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
187
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(203 citation statements)
references
References 60 publications
9
187
1
6
Order By: Relevance
“…With fewer inflammatory cytokines produced in the bowel, the liver may produce less CRP, resulting in lower concentrations of CRP (Rosamond, 2002). In agreement with recent reviews (Bastard et al, 2006;Ma et al, 2008), two studies in this review found simultaneous reductions in CRP and IL-6 (Esposito et al, 2003a.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With fewer inflammatory cytokines produced in the bowel, the liver may produce less CRP, resulting in lower concentrations of CRP (Rosamond, 2002). In agreement with recent reviews (Bastard et al, 2006;Ma et al, 2008), two studies in this review found simultaneous reductions in CRP and IL-6 (Esposito et al, 2003a.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the risk reduced by 61% (P-value for trend ¼ 0.006) for subjects in the highest quartile of watersoluble intake and 75% (P-value for trend o0.01) for insoluble fibre (Ma et al, 2006). However, more recently, Ma et al (2008) reported no association between DF and CRP among post-menopausal women enrolled in the Women's Health Initiative Observational Study although intakes of DF were inversely associated with other markers of systemic inflammation (interleukin (IL)-6 and tumour necrosis factor-a receptor-2). DF may therefore play an important role in mediating the relation between diet, inflammation and cardiovascular disease (King et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…In addition, single food components have been found to be related to inflammatory markers; higher intakes of dietary fibre (Ma et al, 2008;Herder et al, 2009;Wannamethee et al, 2009), whole-grain products (Qi et al, 2006;Lutsey et al, 2007), fruit and vegetables (Wannamethee et al, 2006;Holt et al, 2009), nuts (Salas-Salvado et al, 2008;Casas-Agustench et al, 2010), and a moderate alcohol intake (Wang et al, 2008;Oliveira et al, 2010) were associated with lower concentrations of several immune mediators in the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…This legume-mediated reduction in CRP (and IL-6) is clinically significant and comparable to that seen with statin therapy [16]. That this anti-inflammatory effect is mediated through the high fibre content of legumes is supported by numerous cross-sectional and longitudinal studies that have shown high-fibre diets are associated with lower systemic inflammation [70][71][72]. We conclude that there is substantial evidence supporting the proposition that high legume consumption has an anti-inflammatory effect that is probably mediated through its high fibre content.…”
Section: The Hispanic Paradoxmentioning
confidence: 70%